Rancangan Master Plan Sistem Teknologi Informasi Pada Dinas Komunikasi dan Informatika Kabupaten Nganjuk Menggunakan Metode Ward and Peppard - Lafirda, Niar Ismi; Amrozi, Yusuf; Milad, M.Khusnu (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
In the Main Duty communications services assist the regent in carrying out some of the household affairs of the region in the field of communication and informatics. Of course, required support of information technology and reliable information systems. To ensure that the SI/IT user supports the government, it is necessary to master the SI/IT or strategy design related to SI/IT in the form of a document called the IT masterplan. There are several methods in making the design of Information Technology master plan. In this research using Ward And Peppard method. This method consists of input and output stages. In the input stage there is an analysis of the internal business environment, the analysis of the external business environment, the analysis of the internal SI/IT environment, the analysis of the external SI/IT environment. In this method using SWOT analysis, Value Chain analysis, and Mc. Farlan Grid analysis. The result of this research is output stage consist of 24 SI strategy, 5 IT strategy, and 2 SI/IT management strategy. From these findings is expected Dinas Kominfo Nganjuk can apply this Information Technology in accordance with business needs Dinas Kominfo Nganjuk. Keywords: Design master plan, Information technology, Ward And Peppard, Dinas Kominfo Nganjuk